Small Cell Neuroendocrine Carcinoma in Head and Neck - Sondang Nora Harahap; Daan Khambri (Indonesian Journal of Cancer, 2021)
Introduction: Poorly differentiated neuroendocrine carcinomas (NECs) originating from the eye are rare and very highly malignant diseases with a poor prognosis. Small cell NEC of the head and neck is a rare disease and highly aggressive. Early recognition and treatment are crucial for reducing morbidity and mortality. Case Presentation: A 19-year-old male visited our oncology surgery outpatient department due to the progressive neck mass enlargement originating from the eye. The patient was previously diagnosed with invasive choroid malignant melanoma of the left eye which had metastasized to the lymph nodes of the left neck. He underwent a surgical removal/exenteration of the left eye. The result showed that the patient’s survival with poorly differentiated tumors was about 14% while patients with well-differentiated NEC had a survival rate of 34%. It also indicates that the prognosis of these tumors is very poor with a total of over 90% of patients having distant metastatic disease. Histopathological examination showed the tumor tissue and its immunohistochemistry with positive streaks of CD56, NSE, Synaptophysin, and Ki67 suggested small cell NEC.Conclusions: it is crucial to establish an early diagnosis of these tumors to reduce morbidity and mortality. No optimal treatment for such disease has yet been established.